The Evolution of Classical Spiro-OMeTAD: Synthesis of Arylamine Endcapped Indenone Spirofluorene - Liu, Shihui; Yi, Xiaoqing; Wang, Hao; Ye, Tao; Wang, Kui; Cao, Wei; Guan, Jing; Fan, Ruiqing; Yang, Yulin; Hao, Sue; Xia, Debin (Frontiers in Chemistry, 2022)
Spiro-OMeTAD is the well-known hole transporting material (HTM) in perovskite solar cells. In this work, its derivatives, namely four D-A shaped triphenylamine or biphenylamine endcapped indenone spirofluorene (SFD-TPA, SFD-OMeTPA, SFD-TAD, and SFD-OMeTAD), were designed and synthesized. With the introduction of electron-donating moieties and the extension of conjugation length, a series of changes in photophysical and electrochemical properties could be detected. Notably, in comparison with the optical gap (2.96 eV) of the reported spiro-OMeTAD, SFD-OMeTAD presents an optical gap as low as 1.87 eV. Moreover, density functional theory simulations were employed to further investigate their geometric and electronic structures. Finally, steady-state photoluminescence measurements proved the efficient charge separation and collection processes at the perovskite/HTM interface. It can be predicted that all four compounds with enhanced sunlight absorption capability and suitable frontier energy levels can be used as hole-transporting materials for perovskite solar cells.